Tongue-tied: Language-based exclusion at a South African university - Sive Makeleni (Interdisciplinary Journal of Sociality Studies)
The post-apartheid government in South Africa adopted a multilingual education policy to provide education in learners' home languages as a foundation for learning while promoting proficiency in at least two additional official languages. This marked a paradigm shift from the apartheid regime, which was characterised by racial segregation and discrimination, prioritising Afrikaans and English at the expense of indigenous African languages. Although widely celebrated, achieving the multilingual promise ushered in by the democratic dispensation remains a challenge for post-apartheid South African higher education. This study explored students' experiences of language-based discrimination at a selected South African university. Using a qualitative approach, data were collected from 20 purposively sampled final-year students through an open-ended questionnaire that was distributed electronically to students in the Education faculty and analysed thematically. The findings revealed that minority language speakers grappled with feelings of invisibility, alienation, frustration, and exclusion in their academic and social lives, making it difficult for them to engage fully in university life. Various coping mechanisms were also reported, demonstrating the agency of these minority groups; however, these were found to be insufficient. The study thus recommended prioritising inclusive language policies and training that foster lingua-cultural empathy among students and staff, among other things.